The effectiveness of self-regulated learning education on Executive functions of dyslexic students - zahra nazari; تقی جباری فر; kazem barzegar (Ravānshināsī-i Afrād-i Istis̠nāyī, 2017)
The aim of this study was to examine the self-regulated learning education on executive functions and reading performance of dyslexic students in fifth grade of Yazd. The study population included all fifth students in Yazd in academic year 2015 – 2016 that were dyslexia. The research method was experimental with pretest-posttest on two experimental and control groups. Sampling was done in two stages. 30 dyslexic students were diagnosed of being dyslexia by specialists of learning disability by use of sampling method were selected and divided into two experimental group (n = 15) and control one (n = 15). The research instrument for data collection was Coolidge neurological questionnaire and the checklist to diagnose dyslexia. Teaching self-regulated learning were conducted on experimental group during 14 sessions of 45 minute twice a week. Results of examining the hypothesis by use of analysis of covariance (significance level = 0/05) indicated that teaching self-regulated learning has effect on executive functions (planning, organizing and pregnancy) of dyslexic students and it has improved them. Self-regulated learning education can be used to improve executive functions of dyslexic students.